(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Sub-acute toxicity study of Ficus racemosa Linn aqueous leaf extract was carried out in this study, a herb which has wide application for treatment of various ailments including hyperglycaemia, gastritis, asthma, dysentery, menorrhagia, glandular enlargement and sore throat. In this study, the first group of rats served as the control group while the other two groups were given F. racemosa L. leaf aqueous extract (FRLAQE) at doses of 100 and 200 mg kg-1 bodyweight, respectively via daily oral gavages for 28 days. Animals of all groups were sacrificed on 29th day of experimentation. For various haematological and biochemical parameters blood samples were collected to determine haemoglobin, WBC count, RBC count, PCV, ESR, bleeding time, clotting time, blood glucose, serum creatinine, urea, total bilirubin and direct bilirubin. Gross and histological examination of kidney, liver, heart, spleen and brain sections was done by veterinary pathologist. Statistics: ANOVA followed by Tuckey’s HSD procedure were used to analyse the data. Haematological and biochemical study did not show any toxic effects following treatment. Pathologically, the extract was found to be non-toxic as no gross and histopathological abnormalities were observed.